Haplotype Homozygosity and Derived Alleles in the Human Genome - Fry, Andrew E. (The American Society of Human Genetics, 2006)
Haplotype-based techniques are being used to estimate the relative age of alleles—particularly in screening loci for signals of recent positive selection—but does this approach capture even coarse age differences? Using simulations and empirical data from the International HapMap Project, we show that a simple pairwise metric of haplotype homozygosity gives significantly higher mean values for human single-nucleotide–polymorphism alleles that appear to be derived than for those that appear to be ancestral, as determined by comparison with the chimpanzee genome. Our results support the use of haplotype-based techniques, such as extended haplotypic homozygosity, to assess the age of alleles.